Non-Profit Organization Project Selection Process Using the Hygiene Method of Multi-Criteria Decision Making - Radhi, A. R.; Burhan, A. M. (Engineering, Technology & Applied Science Research, 2022)
With the fast increase in technological development and society's needs, using Multi-Criteria Decision Making (MCDM) as a solution to tackle problems faced during a project's life cycle in different engineering fields gains interest. The use of artificial intelligence gave new opportunities to deal with problems faced during the optimization of unknown or known solutions and methods. Even more, the application of optimized solutions can be developed or modified by using different optimization approaches and methods. This paper proposes a model for the project selection process for non-profit organizations that have a limited budget and social factors strictly related to the selection process. This method is based on MCDM and takes into consideration criterion weights and experts' evaluation of projects according to the selection criteria using the hygiene method consisting of two stages, fuzzy logic, and TOPSIS.